Energy dissipation in high-energy ship-offshore jacket platform collisions - Travanca, J.; Hao, Hong (Elsevier Ltd, 2015)
Ship collisions with offshore structures may be characterized by large amounts of kinetic energy that can be dissipated as strain energy in either the ship, or the installation, or shared by both. In this paper a series of FE numerical simulations are performed with the aim of providing a clearer understanding on the strain energy dissipation phenomenon, particularly upon the ship-structure interaction. Ships of different dimensions and layouts are modelled for impact simulations. Likewise, three platform jacket models of different sizes and configurations are considered. The collision cases involve joints, legs, and braces and are simulated for several kinetic energy amounts of the vessels and different impact orientations. An overview of the plastic deformation mechanisms that can occur in both ship and jacket structure is also given. The results from the various models with different collision scenarios are compared in terms of the strain energy dissipation with respect to the different ship/installation strength ratios. From the FEA simplified approaches are also derived in terms of the relative stiffness of the two structures for assessing the responses and energy absorptions of the two structures. The conclusions drawn from this study can be applied to a broader range of collision assessment of offshore steel jacket platforms subjected to high-energy ship impacts.